THE EFFECT OF ANXIETY LEVELS OF TYPE 2 DIABETES MELLITUS PATIENTS ON THEIR TREATMENT ADHERENCE IN THE COVID-19 PANDEMIC PERIOD - Zeynep Büşra Teke; Sibel Şentürk; Alev Yıldırım Keskin (Rojan GÜMÜŞ, 2022)
This study was conducted to investigate the effects of the anxiety levels of Diabetes Mellitus (DM) patients on their treatment adherence in the COVID-19 pandemic period. The sample of this descriptive and cross-sectional study consisted of 313 DM patients who presented to the internal medicine outpatient clinic between 01.01.2021 and 01.02.2021. The data were collected using a Personal Information Form, the Coronavirus Anxiety Scale (CAS), and the Morisky Medication Adherence Scale (MMAS-8). Descriptive statistics, Mann-Whitney U test, Kruskal-Wallis test and Spearman's correlation test were used to analyze the data. The mean CAS score of the DM patients was 7.89±3.87, while their mean total MMAS-8 score was 4.06±1.56. It was determined that the patients who were using oral antidiabetic medications, those adhering to their medication and diet treatment, and those who were not COVID-19 had higher levels of anxiety. There was a negative significant relationship between the MMAS-8 and CAS scores of the patients (p